2014
DOI: 10.1093/jjco/hyu121
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase Gene Polymorphisms and Susceptibility to Acute Myeloid Leukemia: Meta-analyses

Abstract: Objective: A large body of evidence has shown the possible relevance of polymorphisms of the genes that encode glutathione S-transferase m, p and u (GSTM1, GSTP1 and GST1, respectively) to the susceptibility of acute myeloid leukemia, but the exact association still remains uncertain. Therefore, we performed a meta-analysis to derive a more precise estimation of the relationship. Methods: A comprehensive literature search of PubMed and Web of Knowledge electronic databases was conducted to collect relevant stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
2
14
0
2
Order By: Relevance
“…In contradiction, in a meta-analysis performed by Tang et al GSTP1 polymorphism was not associated with acute leukemia risk in Asians [ 18 ]. Similar results to those reported by Tang et al were observed by He et al [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contradiction, in a meta-analysis performed by Tang et al GSTP1 polymorphism was not associated with acute leukemia risk in Asians [ 18 ]. Similar results to those reported by Tang et al were observed by He et al [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contradiction, a recent meta-analysis performed by He et al showed that GSTM1 null genotype was associated with the risk of developing AML in East Asians while GSTT1 null genotype was a risk factor for AML in Caucasians [ 37 ]. The same study revealed that the presence of both GSTM1 and GSTT1 null genotypes might increase significantly the risk of AML in both Asians and Caucasians [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of GST isoenzymes were studied in various disease states, and null gene expression was implicated as a susceptibility factor for particular diseases [ 7 , 12 , 13 ]. However, GST isoenzyme polymorphisms were also studied in a number of dermatologic diseases to be able to account for increased disease susceptibility with regard to null enzyme expression [ 6 , 8 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… Rollinson et al (2000) reported that there was an association between the null GSTT1 and the null GSTM1 genotypes and the risk of developing AML. In a meta-analysis, it was suggested that the presence of the dual null genotype GSTM1 - GSTT1 increased the risk of developing AML in both the Caucasians and the East Asians ( He et al, 2014 ). Lemos et al (1999) showed that there was no statistically significant relationship between the GSTM1 gene status and the development of CLL.…”
Section: Discussionmentioning
confidence: 99%